1995
DOI: 10.1038/ng0595-99
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal gene product identified in hereditary dentatorubral–pallidoluysian atrophy (DRPLA) brain

Abstract: Dentatorubral-pallidoluysian atrophy (DRPLA) is associated with the expansion of an unstable CAG repeat. Using antibodies against a synthetic peptide corresponding to the sequence of the DRPLA gene product C terminus, we have identified the DRPLA gene product in normal human brains as a approximately 190 kD protein. We also find a larger approximately 205 kD protein specifically in DRPLA brains. Immunohistochemically, the DRPLA gene product is observed mainly in the neuronal cytoplasm. Our results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 33 publications
3
85
0
Order By: Relevance
“…Although proteins containing expanded polyglutamine domains are expressed in virtually every tissue, they appear to cause cell death only in the central nervous system [16,17] and in a transiently transfected mammalian cell line [13]. In this paper we demonstrate that expression of long polyglutamine repeats (59-81 residues) in GST-fusion proteins causes lengthand concentration-dependent inhibition of cell growth in E. coli.…”
Section: Discussionmentioning
confidence: 92%
“…Although proteins containing expanded polyglutamine domains are expressed in virtually every tissue, they appear to cause cell death only in the central nervous system [16,17] and in a transiently transfected mammalian cell line [13]. In this paper we demonstrate that expression of long polyglutamine repeats (59-81 residues) in GST-fusion proteins causes lengthand concentration-dependent inhibition of cell growth in E. coli.…”
Section: Discussionmentioning
confidence: 92%
“…It has a nuclear localization signal (NLS) in the N-terminus and a nuclear export signal (NES) in the Cterminus, which allow both nuclear and cytoplasmic localization of the protein (Yazawa et al, 1995(Yazawa et al, , 1997Okamura-Oho et al, 1999;Nucifora et al, 2003). In Drosophila, Atrophin acts as a transcription co-repressor in regulating segmentation and planar polarity during embryonic development (Zhang et al, 2002;Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Yazawa et al (1995) identified the DRPLA gene product in normal human brains as a ~ 190 kD, and in DRPLA brains as a larger ~205 kD [184].…”
Section: Paroxysmal Nocturnal Hemoglobinuria (Pnh)mentioning
confidence: 99%